Spatiotemporal distribution of the seismicity along the Mid-Atlantic Ridge north of the Azores from hydroacoustic data: Insights into seismogenic processes in a ridge-hot spot context - Goslin, J. (2018)
The seismicity of the North Atlantic was monitored from May 2002 to September 2003 by the 'SIRENA array' of autonomous hydrophones. The hydroacoustic signals provide a unique data set documenting numerous low-magnitude earthquakes along the section of the Mid-Atlantic Ridge (MAR) located in a ridge-hot spot interaction context. During the experiment, 1696 events were detected along the MAR axis between 40 degrees N and 51 degrees N, with a magnitude of completeness level of m(b) approximate to 2.4. Inside the array, location errors are in the order of 2 km, and errors in the origin time are less than 1 s. From this catalog, 15 clusters were detected. The distribution of source level (SL) versus time within each cluster is used to discriminate clusters occurring in a tectonic context from those attributed to non-tectonic (i.e. volcanic or hydrothermal) processes. The location of tectonic and non-tectonic sequences correlates well with regions with positive and negative Mantle Bouguer Anomalies (MBAs), indicating the presence of thinner/colder and thicker/warmer crust respectively. At the scale of the entire array, both the complete and declustered catalogs derived from the hydroacoustic signals show an increase of the seismicity rate from the Azores up to 43 degrees 30'N suggesting a diminishing influence of the Azores hot spot on the ridge-axis temperature, and well correlated with a similar increase in the along-axis MBAs. The comparison of the MAR seismicity with the Residual MBA (RMBA) at different scales leads us to think that the low-magnitude seismicity rates are directly related to along-axis variations in lithosphere rheology and temperatures.